Liquid crystal technologies for enhanced optical system functionality - Jin, Y (2023)
This thesis aims to investigate and develop novel liquid crystal (LC) technologies that can either manipulate the optical wavefront (phase) of light in a controlled way or improve the imaging quality by reducing the appearance of laser speckle by manipulating the optical wavefront in a pseudo-random way. Control of these properties is of great importance for a vast range of photonics and optics applications; for example, in LC spatial light modulators (LC-SLMs), near-eye displays, laser projectors and biomedical microscopes. Among these applications, laser sources have been an indispensable element in modern imaging applications. This is because they exhibit many essential features (e.g., a high intensity, a narrow spectral linewidth, and directionality). However, due to the high coherence of laser light, the issue of speckle arises, which can badly plague the clarity and the appearance of an image. The essential reason for such degradation is because the coherent laser light will scatter when it interacts with an optically rough surface and forms constructive or destructive interference on the imaging plane.